Exploring the phenomenology of the embodiment of the virtual self, using immersive virtual reality - Ajodhya, Sachin Adarsh (University of the Witwatersrand, Johannesburg, 2025)
Immersive Virtual Reality (IVR) has emerged as a novel tool to experimentally study the sense of body ownership (feeling that my body belongs to me) and bodily self-awareness (agency, I am the initiator of my actions) using virtual worlds and bodies (i.e. avatars). Recent studies have shown that embodiment of a White participant in a Black avatar can reduce implicit racial bias. However, no study to date has drawn on a sample of Black participants to explore and measure embodiment experiences or changes in attitude using IVR. Furthermore, only a handful of IVR studies have used qualitative methods to explore the in-depth subjective experience of virtual embodiment. Guided by Embodied Cognition Theory, this study aimed to explore subjective experiences of female and Black-identifying participants (n=8) embodying another raced virtual body using IVR. Semi-structured qualitative interviews and quantitative psychological questionnaires were used following an IVR experience. Quantitative data was (only) used at superficially level to aid in qualitative descriptions. Drawing on Braun and Clarke’s reflexive thematic analysis, three main themes were identified, namely: (1) self-awareness; (2) embodiment experiences; and (3) other-awareness. Participants reported a complex interplay between embodiment experiences and emotion in creating a sense of self in the context of the other in the virtual environment. Interestingly, topics around race were not organically shared by the participants during the interviews. Furthermore, qualitative accounts elicited much richer narratives on embodiment compared to the quantitative questionnaire to include experiences around the ‘digital divide’ (i.e., first-time experiences with IVR), place illusions (i.e., strong illusion of being in a specific place despite not being there), plausibility illusions (i.e.., illusion that IVR and events are real) and hybrid racial identities (i.e., the “coconut effect”). The results of the study call for increased diversity in IVR research to include more representative samples and to integrate qualitative methods to understand the complex processes involved in studying embodied self-awareness using IVR.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts (Coursework and Research Report), Department of Psychology, to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2025
Keywords: Embodiment; Self-awareness; Other awareness; Race; Immersive Virtual Reality; UCTD; SDG-3: Good health and well-being; SDG-9: Industry, innovation and infrastructure